Donor liver natural killer cells ameliorate liver allograft rejection via inducing apoptosis of alloreactive CD8+ T cells generating CD4+CD25+ regulatory T cells - Jiandong Yu; Jiayan Wu; Tianzhu Long; Lihong Lv; Zhiping Chen; Zeyu Lin; Hongquan Zhu; Guolin Li; Yunle Wan (Scientific Reports)
Abstract The roles of donor liver natural killer (NK) cells in allogeneic liver transplantation remains controversial. Herein, we investigated the effects of liver NK cells on liver allograft tolerance by using liver NK cells and allogeneic spleen T cell co-culture in vitro experiments and the rat orthotopic liver transplantation model. CD8+ T cells exhibited higher apoptotic rate and up-regulated expression of CD95 molecules when co-cultured with allogeneic liver NK cells in vitro, indicating that liver NK cells might induce the apoptosis of CD8+ T cells via CD95 in vitro. The rat liver transplant model showed that recipients with donor liver NK cell immunity, had better survival, less damage, and higher apoptotic rate of intrahepatic infiltrating lymphocytes in liver grafts, as well as higher level of peripheral CD4+CD25+ T cells and lower level of peripheral CD3+CD8+ T cells. These findings indicate that donor liver NK cells can ameliorate allograft rejection via inducing the CD95-mediated apoptosis of alloreactive CD8+ T cells and the generating of CD4+CD25+ regulatory T cells.